Minecraft for Education: Promoting Social and Emotional Learning in Mathematics - Yanuarto, Wanda Nugroho; Setyaningsih, Eka; Wahyuningsih, Purwanti (Jurnal Pendidikan Indonesia, 2023)
The usage of games, which have been around for a very long time and have been the focus of research for a number of years, is a component of mathematical education. The usage of games in mathematics classrooms is far higher than in any other subject. Furthermore, teachers agree that video games are an excellent medium for teaching mathematics in middle school. This raises the question of whether students in the secondary grades change their mathematical identities as a result of participating in an inquiry-based teaching unit with Minecraft. The information whether students in the secondary grades change their mathematical identities as a result of participating in an inquiry-based teaching unit with Minecraft remains unclear. The aims of this study is to analyze information regarding the benefits of using Minecraft as a teaching tool, the challenges that come with it, the viewpoints of students on the game, and the educational benefits it provides. The current study was based on a Minecraft-based teaching unit that was carried out in a class with a total of 22 high school students. This study use semi-structured interviews in our qualitative research endeavor. This study project's findings researcherre put into three themes, they are 1) students of mathematics; 2) Minecraft gamer of mathematics students; and 3) repositioned as students of mathematics.